Children's Dental anxiety after cavity preparation - Camille Torres Costa Ferreira; Francielle Ribeiro Alves; Thuanny Castilho; Leonardo Santos Antunes; Marlus Roberto Rodrigues Cajazeira; Lívia Azeredo Alves Antunes (Associação Brasileira de Odontologia, 2018)
The purpose of this series of case reports was to evaluate the anxiety generated in pediatric patients submitted to two mechanical techniques of cavity preparation: the conventional rotary instruments (i.e. high and low speed) using diamond tips and ultrasonic abrasion using CVD™ system tips. To this end, 04 patients aged 06-09 years had at least two deciduous molars with occlusal caries were selected for this study. The teeth were randomly divided into two experimental groups CVD (CVD system with cavity preparation) and CRI group (cavity preparation with rotary instruments). The preparation procedures were performed under local anesthesia and rubber dam and cavities restored with composite resin. At the beginning and end of each visit, a closed questionnaire which aimed to assess the child's anxiety during the visit in which each preparation technique was used was applied. The results were submitted to descriptive statistical analysis. According to the results it was found that dental consultation and local anesthesia were of concern in all patients. The two preparation techniques resulted in similar patterns of anxiety both before and after use. Within the limitations of this study, it can be concluded that all the factors involved in dental appointment contribute to make it a cause for concern among pediatric patients.